Surface patch binding‐induced exfoliation of nanoclays and enhancement of physical properties of gelatin organogels. Issue 2 (8th November 2016) - Sharma, Anshu; Rawat, Kamla; Solanki, Pratima R; Bohidar, Himadri B
Abstract: Nanoclay‐containing organogels were prepared by exfoliating layered silicate nanoclay (Laponite ® and montmorillonite, aspect ratio 30 and 250) in organogels made in glycerol solutions. Zeta potential of the binding profile between clay and gelatin chains in the milieu of glycerol was consistent with a surface patch binding mechanism. To achieve customized thermal and viscoelastic properties, optimum binding of nanoclay to gelatin was probed, and it was noticed that [clay] = 0.03% (w/v) and [glycerol] = 30% (v/v) produced the best results. Gelation temperature T gel (Laponite organogels) increased from 28 to 34 °C ( ca 21% change) with a concomitant increase in gel elastic modulus from 400 to 1200 Pa ( ca 300% change). For montmorillonite organogels, it was possible to raise T gel further to 43 °C (56% change). X‐ray diffraction data and Cole–Cole plots indicated that clay platelets were homogeneously exfoliated in the organogel matrix. Thus, the thermoviscoelastic properties of gelatin organogels could be modulated to raise the gelation temperature to 43 °C, and gel strength to 1200 Pa by the addition of nanoclay whose concentration may not exceed 0.03% (w/v). Considering the wide application of gelatin gels in pharmaceuticals, food preservation and personal care products, the aforesaid enhancement in physical properties is significant. © 2016 Society of Chemical Industry Abstract : Schematic depiction of self‐assembly of gelatin and clay in organogel.